Conservation of Local Languages Through the Al-Qur'an Juz 30 Translation Learning Program in Balinese - Rusmayani Rusmayani; Novena Ade F.S; Arjiman Arjiman (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2026)
Found that there was an increase in speaking and reading skills from 4 as-pects of language skills in learning the Translation of the Qur'an Juz 30 in Balinese, so it is necessary to explore the methods and approaches used in the learning activities. The purpose of this study was to describe: 1) The method of learning the Balinese Translation of Juz 30 as a form of preserv-ing the Balinese Regional Language, and 2) The Balinese Immersion Approach through Community Service Programs (KKN). The method used is descriptive qualitative, informants are determined purposively. Data collec-tion techniques use observation and interviews. Furthermore, the data is analyzed by sorting data, organizing it, and presenting it. This study found that: 1. The methods used in learning the Balinese Translation course Juz 30 are lectures, repeated exercises, and vocabulary deposits, these three methods are used simultaneously and sequentially, 2) Balinese Immersion through KKN activities is actively interacting with the local community through Community Service Programscontained in the work program, both work programs initiated by students based on community needs and village work programs, students are also active in helping the Hindu community install penjor before the Galungan and Kuningan celebrations.